KEMAMPUAN MENGAPRESIASI DONGENG ”NAMBORU SARODING” OLEH SISWA KELAS V SD NEGERI 173194 BATUMANUMPAK TAHUN PEMBELAJARAN 2018/2019 - Ipan Sihite; Berliana Simanjuntak (JURNAL ILMIAH EDUNOMIKA, 2023)
This research aims to describe the ability to appreciate the fairy tale "Namboru Saroding" by fifth grade students at state elementary schools. 173210 Sigotom 2018/2019 Academic Year. The population in this study was class V students at SD Negeri 173194 Batumanumpak, totaling 21 students. And the research sample was a population of 21 people. The method used in this research is descriptive method. The research data collection tool is to appreciate the fairy tale "Namboru saroding". By providing 10 multiple choice questions with four options regarding theme, message, plot, setting, characterization and character. Based on the results of the analysis of the data obtained by the author after obtaining the scores and ability scores of fifth grade elementary school students, the researcher concluded that the average score of students' ability to appreciate the fairy tale "Namboru saroding" was 72.38. This average value, when consulted with the established criteria, turns out to be in category B (Good). Keywords : Fairy tale.